Bacillus aquiflavi sp. nov., isolated from yellow water of strongly flavored Chinese baijiu. Issue 5 (4th May 2020) - Xie, Jiuyan; Cheng, Kun; Zhao, Dong; Yang, Guanrong; Qiao, Zongwei; Qiu, Shengqiang; Yu, Xuejian; Liu, Hongqiang; Li, Ting; Feng, Huijun; Yao, Su; Zhai, Lei
Abstract : A Gram-stain-positive, strictly aerobic and rod-shaped bacterium, designated as 3 H-10 T, was isolated from a yellow water sample collected from the manufacturing process of strong flavor Chinese baijiu in Yibin region of Sichuan province (PR China). Oval endospores were formed at the subtermini of cells with swollen sporangia. The isolate was able to grow at temperatures of 20–45 °C (optimum growth at 37 °C), at pH 6.0–10.0 (optimum growth at pH 8.0) and in the presence of 0–2 % (w/v) NaCl (optimum growth with 0 % NaCl). Ribose was the major cell-wall sugar, and meso -diaminopimelic acid ( meso -DAP) was the diagnostic amino acid. The main polar lipids of 3 H-10 T included diphosphatidylglycerol (DPG), phosphatidylglycerol (PG) and phosphatidylethanolamine (PE). MK-7 was predominant menaquinone and iso-C15 : 0 (60.7 %) was the major fatty acid. Comparisons of 16S rRNA gene sequence indicated that 3 H-10 T was most closely related to Bacillus mesophilus SA4 T (96.30 %), Bacillus ginsengihumi Gsoil 114 T (96.27 %) and Bacillus shackletonii LMG 18435 T (96.27 %). The average nucleotide identity (ANI) values between strain 3 H-10 T and the three type strains mentioned above were 69.56, 70.19 and 70.67 %, respectively. The genomic DNA G+C content was 35.4 mol%. On the basis of its phenotypic, chemotaxonomic and phylogenetic properties, strain 3 H-10 T represents a novel species of the genus Bacillus, for which the name Bacillus aquiflavi sp. nov. is proposed. The type strain is Bacillus aquiflavi 3 H-10 T (=CICC 24755 T =JCM 33703 T ).